1990
DOI: 10.1135/cccc19901033
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of methyl tert. butyl ether synthesis in gaseous phase

Abstract: Kinetics of methyl tert.butyl ether synthesis from methanol and isobutene was measured in gaseous phase at 85 °C and atmospheric pressure on macroreticular ion exchanger catalyst containing strongly acidic functional groups SO3H and on the same catalyst partially neutralized by sodium and iron ions. The form of the best Langmuir-Hinshelwood type kinetic equation suggests absorption of the reactants in the polymer mass causing ìswellingî of it and influencing the accessibility of active sites by the reactants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…This fact hinders the screening of an only model for the reaction. Both mechanisms, which only differ in the adsorption model for isobutene, are very similar and agree with the conclusions of Tejero et al (1989), Setinek (1987), and Hejmankova et al (1990) on the homologous reaction for obtaining MTBE. The former studied the reaction at 41-61.8 °C and 0.02-0.3 atm of pressure of reactants and proposed a mechanism whose rate-determining step was the surface reaction between the methanol adsorbed on one center with isobutene adsorbed on two sites.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This fact hinders the screening of an only model for the reaction. Both mechanisms, which only differ in the adsorption model for isobutene, are very similar and agree with the conclusions of Tejero et al (1989), Setinek (1987), and Hejmankova et al (1990) on the homologous reaction for obtaining MTBE. The former studied the reaction at 41-61.8 °C and 0.02-0.3 atm of pressure of reactants and proposed a mechanism whose rate-determining step was the surface reaction between the methanol adsorbed on one center with isobutene adsorbed on two sites.…”
Section: Resultssupporting
confidence: 89%
“…Standard adsorption enthalpy and entropy values deduced from literature data are also very close to those obtained from models 3 and 4. With regard to the adsorption equilibrium constant of isobutene, values reported at 85 °C by Setinek (1987) and Hejmankova et al (1990) are closer to values found at 78.5 °C for models 3 and 4, with the values of models 1 and 2 being somewhat higher, particularly for model 2. Besides, values obtained by extrapolation of Kx data obtained in the kinetic study of the addition of methanol to isobutene on Amberlyst 15 at 41.0-61.5 °C are of the same order of magnitude as those Both adsorption models proposed for isobutene are possible from a physical standpoint at the working temperatures and even could take part simultaneously.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The high-performance ion-exchange resins of practical importance have been synthesized since two chemists (Adams and Holmes, 1935) discovered that the condensation products of phenol and formaldehyde exhibit ion-exchange properties. To date, ion-exchange resins have found practical applications in a number of areas and are particularly used as catalysts for hydration (Ihm et al, 1988;Velo et al, 1990), hydrolysis (Fuchigami, 1990), alkylation (Kim and Ihm, 1982;Park and Ihm, 1985;Patwardhan and Sharma, 1990a), esterification (Petrini et al, 1988;Patwardhan and Sharma, 1990b), dehydration (Chee and Ihm, 1986), etherification (Lee and Ihm, 1987;Hejtmankova et al, 1990;Rehfinger and Hoffmann, 1990;Lee et al, 1991;Parra et al, 1994), and isomerization (Ahn et al, 1988;Li, 1989).…”
Section: Introductionmentioning
confidence: 99%